Tolong-Menolong dalam Kebajikan sebagai Pedoman Masyarakat: Analisis Perspektif Pendidikan Agama Islam - Inang; Ditya Fajrianti; Nasaruddin (STKIP Subang, 2025)
The phenomenon of modernization and individualism has given rise to social values ​​such as mutual assistance (ta'āwun) in community life. In the context of Islamic Religious Education, the value of mutual assistance is not only a moral requirement but also a normative teaching derived from the Qur'an and Hadith. This article aims to analyze the concept of mutual assistance in virtue as a guideline for character formation in society based on Islamic values. This research uses a literature study method by examining various classical and contemporary literature, including interpretations of the Qur'an, Hadith, and modern Islamic education studies. The results of the study indicate that the concept of ta'āwun 'alal birri wat-taqwā embodies the values ​​of social solidarity, empathy, and moral responsibility that form the foundation of civil society. These implemented values ​​can be integrated into Islamic Religious Education learning through role models, habituation, and strengthening social character. This article emphasizes that building a moral society cannot be separated from strengthening long-term values ​​within the Islamic education system. Keywords: Mutual Help, Virtue, Islamic Religious Education, Social Character, Islamic Society.